Muhammadiyah Cultural Da’wah Towards The Kalomba Tradition in Sinjai District (Study of Da'wah Messages) - Vivi Elvira; Hamiruddin Hamiruddin; Suf Kasman (Pascasarjana UIN Alauddin Makassar, 2023)
The cultural da'wah of Muhammadiyah emphasizes the process of dynamization and purification of the developing culture or traditions of society, especially the Kalomba tradition in Erabaru Village, Tellulimpoe District, Sinjai Regency. The Kalomba tradition held for children is used as an obligation that must be carried out so that children do not get skin diseases such as boils, itching, and scabies. In implementing this tradition, several processes are carried out that have symbolic meaning. The aim of this research is to determine the message of Muhammadiyah's cultural da'wah towards the Kalomba tradition in Erabaru Village, Tellulimpoe District, Sinjai Regency. The type of research used was descriptive qualitative research, and the research approach used was a da'wah and communication approach named the Muhammadiyah cultural da'wah. The results of this study show that Muhammadiyah's cultural preaching message towards the Kalomba tradition in Erabaru Village, Tellulimpoe District, Sinjai Regency shows that the symbolic meaning of the process of the Kalomba tradition, which contains good values in accordance with Islamic teachings, must be maintained, developed, and used as an example. Meanwhile, symbolic meanings that are in contrast with Islamic teachings must be fixed and purified again so they can be appropriate to the principles of Islamic teachings. In general, the implementation of the Kalomba tradition is contrary to Islamic teachings because of the food offering, and incense is used as a condition for the validity of the Kalomba and an intermediary for prayer acceptance.